Reduction of Cell Surface T-Cell Receptor by Non-Mitogenic CD3 Antibody to Mitigate Murine Lupus - Morita, Masashi; Mizui, Masayuki; Masuyama, Satoshi; Tsokos, George C.; Isaka, Yoshitaka (Frontiers in Immunology, 2022)
T-cells are critically involved in the pathogenesis of systemic lupus erythematosus. Although treatment with anti-CD3 antibody has been reported to be effective in several autoimmune disease animal models including lupus, the immunosuppressive mechanisms remain obscure because of its pleiotropic in vivo kinetics. In this study, a conventional anti-CD3 (2C11C) and a non-mitogenic anti-CD3 with manipulated Fc region (2C11S) were compared to elucidate the underlying mechanism of action. Efficacy and safety of 2C11S in vivo were demonstrated by sustained TCR reduction for longer period as compared to 2C11C, and no induction of cytokine release or T-cell depletion. Anti-CD3s were administered to NZB/W F1 (BWF1) mice at different time points for individual periods. The short-term treatment with 2C11S in the early phase of lupus suppressed autoantibody associated with reduction of germinal center B-cells. Treatment in the late phase attenuated lupus nephritis without affecting autoantibodies or differentiation of effector T-cells. The effect of reduced TCR in the development of autoimmunity was examined by CD3z heterozygous-deficient mice, in which T-cells had reduced TCR intensity but showed normal TCR signaling response. Autoantibody and lupus nephritis were attenuated significantly in CD3z heterozygous-deficient lupus-prone mice. Collectively, reduction of surface TCR by non-mitogenic anti-CD3 could sufficiently suppress the development of lupus.